2020
DOI: 10.3389/fnins.2020.00336
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Task fMRI Signals for Variability in Baseline CBF Improves BOLD-Behavior Relationships: A Feasibility Study in an Aging Model

Abstract: Sensitizing Task-fMRI Signals in Aging task designs is necessary to improve the stability of predicting associated behavior. In summary, we recommend correction of task fMRI signals by covarying out baseline CBF especially when comparing groups with different neurovascular properties. Given that ASL and BOLD fMRI are well established and widely employed techniques, our proposed multi-modal methodology can be readily implemented into data processing pipelines to obtain more accurate BOLD activation maps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 62 publications
1
29
1
Order By: Relevance
“…From this viewpoint, we have attempted to undertake an integrative physiology approach (that is cerebrovascular control and its integration with other physiological systems such as cardiovascular and pulmonary) to describe the role of CVR, and how understanding the impairment of such mechanisms in various disease models can advance brain rehabilitation programs. Given the versatility of neuroimaging techniques, and that the cerebrovascular control is a complex interplay of various physiological components, it is important to underscore that future work should combine CVR imaging with other neuroimaging approaches that can measure blood flow along with BOLD activity ( Krishnamurthy et al, 2020 ), autoregulation ( Whittaker et al, 2019 ), and brain pH ( Ellingson et al, 2019 ). The future of rehabilitation lies in the search for biomarkers of disease status, progression, and treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this viewpoint, we have attempted to undertake an integrative physiology approach (that is cerebrovascular control and its integration with other physiological systems such as cardiovascular and pulmonary) to describe the role of CVR, and how understanding the impairment of such mechanisms in various disease models can advance brain rehabilitation programs. Given the versatility of neuroimaging techniques, and that the cerebrovascular control is a complex interplay of various physiological components, it is important to underscore that future work should combine CVR imaging with other neuroimaging approaches that can measure blood flow along with BOLD activity ( Krishnamurthy et al, 2020 ), autoregulation ( Whittaker et al, 2019 ), and brain pH ( Ellingson et al, 2019 ). The future of rehabilitation lies in the search for biomarkers of disease status, progression, and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular reactivity can be retrospectively combined with task fMRI data to sensitize the BOLD signals to index neural activity ( Bandettini and Wong, 1997 ; Liu et al, 2013 ). Given that profiling and characterizing behavioral changes is important for cognitive neurorehabilitation, it is important to improve the relationship between neuro-sensitized BOLD maps and relevant behavior ( Krishnamurthy et al, 2020 ). Thus the methodological approach of combining CVR maps with BOLD data is extremely important, and from that perspective, systematic experimental and theoretic work from Liau and Liu (2009) have shown that normalization based on division (i.e., voxel-wise BOLD activity divided by corresponding CVR) approach resulted in increased inter-subject variability.…”
Section: Rehabilitation Relevant Advanced Imaging Approaches Involvinmentioning
confidence: 99%
See 1 more Smart Citation
“…We provided evidence that our novel TCMcorr methodology is more effective in mitigating TCM artifacts compared to other existing approaches, while also being cost efficient to reliably denoise larger data sets. From a clinical translation standpoint, optimal removal of TCM artifacts will allow for subsequent secondary analyses such as quantifying area under the curve (underneath the denoised HRF) to obtain longitudinal BOLD‐behavior relationships (Krishnamurthy, Krishnamurthy, Drucker, et al, 2020) indexing neuroplasticity in response to treatment and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to assess if the BOLD energetics changed as a function of tissue viability, we extracted the unthresholded Z-transformed area under the curve of the HRF (Krishnamurthy et al, 2020(Krishnamurthy et al, , 2021. Briefly, we computed the area under the curve (AUC) of all beta coefficients describing the HRF (12 tent functions that jointly describe the 3dDeconvolve output impulse response function), followed by a Z-transform of the AUC for each participant to normalize the distribution in preparation for parametric statistics.…”
Section: Validation Of Tigr-identified Pericavitational Regions Using Task Fmrimentioning
confidence: 99%